Human Papillomavirus Oncoproteins E6 and E7 Independently Abrogate the Mitotic Spindle Checkpoint - Thomas, Jennifer T. (American Society for Microbiology, 1998)
The E6 and E7 genes of the high-risk human papillomavirus (HPV) types encode oncoproteins, and both act by interfering with the activity of cellular tumor suppressor proteins. E7 proteins act by associating with members of the retinoblastoma family, while E6 increases the turnover of p53. p53 has been implicated as a regulator of both the G(1)/S cell cycle checkpoint and the mitotic spindle checkpoint. When fibroblasts from p53 knockout mice are treated with the spindle inhibitor nocodazole, a rereplication of DNA occurs without transit through mitosis. We investigated whether E6 or E7 could induce a similar loss of mitotic checkpoint activity in human keratinocytes. Recombinant retroviruses expressing high-risk E6 alone, E7 alone, and E6 in combination with E7 were used to infect normal human foreskin keratinocytes (HFKs). Established cell lines were treated with nocodazole, stained with propidium iodide, and analyzed for DNA content by flow cytometry. Cells infected with high-risk E6 were found to continue to replicate DNA and accumulated an octaploid (8N) population. Surprisingly, expression of E7 alone was also able to bypass this checkpoint. Cells expressing E7 alone exhibited increased levels of p53, while those expressing E6 had significantly reduced levels. The p53 present in the E7 cells was active, as increased levels of p21 were observed. This suggested that E7 bypassed the mitotic checkpoint by a p53-independent mechanism. The levels of MDM2, a cellular oncoprotein also implicated in control of the mitotic checkpoint, were significantly elevated in the E7 cells compared to the normal HFKs. In E6-expressing cells, the levels of MDM2 were undetectable. It is possible that abrogation of Rb function by E7 or increased expression of MDM2 contributes to the loss of mitotic spindle checkpoint control in the E7 cells. These findings suggest mechanisms by which both HPV oncoproteins contribute to genomic instability at the mitotic checkpoint.